Understanding Tourism Destination through Music: Digital Engagement Discourse Based on Sentiment Analysis Approach - Singgalen, Yerik Afrianto (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
This research investigates the effectiveness of music-video content as a tool for tourism destination marketing, employing the CRISP-DM framework to approach data collection, analysis, and interpretation systematically. Focusing on the music video "Welcome to Sumba Island" by Marapu Reggae Official, the study analyzes public sentiment and toxicity scores to gauge audience engagement. The findings reveal a predominance of positive sentiments and minimal toxicity, with scores such as 0.02117 for general toxicity and 0.00189 for severe toxicity, indicating a respectful and appreciative audience. The Decision Tree (DT) algorithm, enhanced by the SMOTE operator, demonstrated superior performance in sentiment classification, achieving an accuracy of 95.50% and an AUC of 0.979. While the study's focus on a single music genre and location limits generalizability, it highlights the potential of music videos in tourism marketing. Future research should expand to diverse music genres and destinations and integrate mixed-method approaches for deeper insights. The CRISP-DM framework's effectiveness in this study underscores its value in guiding sentiment analysis and developing impactful tourism marketing strategies